2018
DOI: 10.5114/ms.2018.76872
|View full text |Cite
|
Sign up to set email alerts
|

Body composition assessment by bioelectrical impedance analysis among patients treated with L-dopa for Parkinson’s disease

Abstract: Introduction: Among the consequences of Parkinson's disease are disorders in body composition and weight loss. Aim of the research: An analysis of body composition of patients with Parkinson's disease treated with L-dopa. Material and methods: A group of 32 patients was examined, including 26 (81.25%) females and 6 (18.75%) males. The study was conducted in the Laboratory for Posturology in the Institute of Physiotherapy at the faculty of Medicine and Medical Sciences, Jan Kochanowski University in Kielce. Bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Contrary to the data above, some current study by Wilczyński and Półrola [27] did not confirm BC changes in PD subjects but demonstrated the sex features in fat mass (%), fat-free and muscle mass (kg), visceral fat, and other parameters of BC. Despite the fact that some studies confirmed the presence of sarcopenic obesity in PD subjects, some recent research studies demonstrated that appendicular lean body mass reliably correlated with cerebral cholinergic innervations in PD subjects independent of age [28].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the data above, some current study by Wilczyński and Półrola [27] did not confirm BC changes in PD subjects but demonstrated the sex features in fat mass (%), fat-free and muscle mass (kg), visceral fat, and other parameters of BC. Despite the fact that some studies confirmed the presence of sarcopenic obesity in PD subjects, some recent research studies demonstrated that appendicular lean body mass reliably correlated with cerebral cholinergic innervations in PD subjects independent of age [28].…”
Section: Discussioncontrasting
confidence: 99%
“…In people with Parkinson's disease, falls occur more frequently in the general elderly population [ 1 ]. They are reported as experienced by 38-68%, constituting one of the most significant causes of morbidity and mortality [ 2 , 3 ]. Recurrent falls often cause traumatic consequences and shorten the duration of life in patients with PD by 7 years [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We took into consideration 49 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] in which BMI was assessed, resulting in 5727 patients, 57.3% of whom were men and 40.9% of whom were women. The lowest reported mean BMI was 17.84 kg/m 2 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Many authors opted not to provide information on the exact number of patients at risk of malnutrition or malnourished, only the mean score of the questionnaire for the entire cohort studied [ 13 , 14 , 17 , 19 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 35 , 37 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%